Transnationalisation et pentecôtisme: la force instituante du sens - Corten, André; Molina, Vanessa (Anthropologica, 2022)
This essay demonstrates that through imaginary social significations embodied in precise images, Pentecostalism institutes a new form of space and territoriality. Among other things, it creates transnationalization by investing established frontier practices with new meaning. The institutional force of the Pentecostal imaginary sheds light on the illusion of an economic globalization nudging the planet from its own natural processes and having effects on all levels, including the religious. The metamorphoses of connections to space, which characterize the last decades, are social constructs. Moreover, as Pentecostalism demonstrates, they are rooted outside the dominant economic framework in a social imaginary, giving marginalized masses the possibility of taking control of their universe by giving it meaning. This new meaning is located in the following four Pentecostal images: conversion as construction of self, money as a new form of the sacred, ordinary life as unity and spiritual war as global bond.